SECURITY DILEMMA & ARMs RACE IN SOUTHEAST ASIAN REGION POST-COLD WAR ERA - Muhammad Arsy Ashshiddiqy (Journal of Diplomacy and International Studies, 2019)
The security conditions in the Southeast Asian region are relatively safe, there have never been direct confrontations or head-to-head wars between countries in the region, if ever there had been a confrontation between Indonesia and Malaysia, but its not happen yet. During the cold war era, security in Southeast Asia was guaranteed by the two super power country, which are United States of America and Soviet Union. Some sort of bias think occur in this region, when the cold war ends European countries are committed to reducing their military budget, and the opposite is true in Southeast Asia. After the end of the cold war and the absence of security guarantees from the two countries, Southeast Asian countries began aggressively increasing their military budgets and increasing their defense force capabilities so that the Security Dilemma and Arms Race happen in this region. In particular, Indonesia has experienced an increase in the military budget from year to year, starting from 2007 Rp. 32 T to 2017 108 T. The increasing of military budget also occurs in all Southeast Asian countries, and this is clear evidence of the Security Dilemma and Arms Race in the Southeast Asian region. The research method used is descriptive qualitative research by describing all the phenomena of the research problem empirically. This study aims to explain and analyze the dynamics of Security Dilemma and Arms Race that happen in Southeast Asia, as well as Indonesia's involvement in this phenomenon, thereby increasing the defense budget each year.